Metal–semiconductor yolk–shell heteronanostructures for plasmon-enhanced photocatalytic hydrogen evolution. Issue 9 (13th February 2018) - Lee, Su-Un; Jung, Hayoon; Wi, Dae Han; Hong, Jong Wook; Sung, Jiha; Choi, Sang-Il; Han, Sang Woo
Abstract : The controlled synthesis of metal–semiconductor yolk–shell heteronanostructures with high photocatalytic performance was achieved through a facile aqueous method. Abstract : Plasmonic metal–semiconductor heteronanostructures with controlled topologies have attracted increasing attention as promising platforms for the efficient conversion of solar to chemical energy. Herein, we describe a novel synthesis route toward the formation of heteronanostructures with plasmonic metal yolks and semiconductor shells, which can enable the enhancement of light harvesting efficiency. Au nanorod-CdS yolk–shell nanostructures with well-defined structural configurations were realized by sulfidation and a subsequent cation exchange reaction with pre-synthesized Au nanorod@Ag core–shell nanostructures. The prepared yolk–shell nanostructures showed superior photocatalytic hydrogen evolution performance under visible light irradiation over their core–shell nanostructured counterparts, CdS hollow nanoparticles, and Au nanorods. A series of mechanistic studies on the photocatalysis distinctly corroborated that the pronounced photocatalytic function of the yolk–shell nanostructures is due to the synergism between the radiative relaxation of the plasmon energy of the Au nanorod yolks and the multiple reflections of the incident light within their voids provided by the yolk–shell structure, which can promote the light absorption of CdS that can drive the photocatalysis. This study can provide a new perspective for designing hetero-nanoarchitectures with intended structures and desired functions.